Meningkatkan Stabilitas Lereng Berdasarkan Pengujian Karakteristik Tanah - Mahendra Septa Kuswiantoro; Agata Iwan Candra; Rifqi Sahrul Nurhuda; Abdi Aziz Nurrahman; Ilham Fanani; Muhammad Najmuddin Alkamal (Jurnal Manajemen Teknologi & Teknik Sipil, 2023)
Kediri Regency has diverse potential and wealth, including natural resources, culture, and tourism. One example is the Dolo waterfall located in Jugo Village. In January 2023 there was an avalanche caused by heavy rainfall in the mountainous area of Jugo Village, Mojo District, Kediri. The landslide disrupted road access to tourist attractions, infrastructure and also affected the economy. Several studies have revealed that soil type, shear strength, and soil consistency properties are important in influencing a slope’s stability level. However, the discussion of landslide prevention efforts regarding soil and slope characteristics is still limited. This study aims to determine soil type, consistency properties, shear angle, soil cohesion, and slope safety factors in Jugo Village, Mojo District, Kediri Regency. Research begins with a survey and sampling, then testing is carried out in the laboratory and calculated the slope safety factor (Fs). The results revealed that the characteristics of the soil in Jugo Village influenced the landslides that occurred. Both the type of soil, the consistency limit, and the shear strength of the soil indicate that the slope is unstable, this is also indicated by the calculation value of Fs <1. The results of this study can be used as a reference in planning and carrying out slope stability at that location so as to prevent landslides in the future. The effort that can be done is to change the slope to 35° so that the slope becomes stable.